Chave de identificação dos peixes de riachos da serra do japi (apas jundiaí-cabreúva/sp) - Yoshida, Claudia Eiko; Rolla, Ana Paula Pozzo Rios; Uieda, Virginia Sanches [UNESP]; Esteves, Katharina Eichbaum (Boletim do Instituto de Pesca, 2016)
About 70% of fish species listed as threatened by the Red List of the Brazilian Fauna show no records within conservation units (CUs). Information to assist the identification and the understanding of the ecology of the species are essential to subsidize different management practices and the appropriate monitoring of the conservation areas. Thus, the objective of this study was to compile existing information in the literature about the ichthyofauna of streams in the CU Serra do Japi and develop an identification key for the fish species. The key was developed considering the characteristics of 31 species of the Upper Paraná River Basin, including headwater endemic species, especially three endangered species of the State of São Paulo - Characidium oiticicai, Pareiorhina cf. rudolphi and Pseudocorynopoma heterandria.
Identification key of stream fishes of the serra do japi (jundiaí-cabreúva/sp conservation units)
Keywords: Atlantic forest; Biodiversity; Conservation; Taxonomy; Tietê river basin